JENIS-JENIS BAKTERI POTENSIAL PATOGEN YANG MENGINFEKSI IKAN MAS (Cyprinus carpio) DI KOLAM PATUMBAK KABUPATEN DELI SERDANG (Potential Pathogen Bacteria Infecting Goldfish (Cyprinus carpio) in Patumbak Pond Deli Serdang Regency) - Meirani Ritonga; Dwi Suryanto; Yunasfi Djayus (AQUACOASTMARINE, 2017)
Goldfish is commonly found in Indonesia. Pest and disease infected goldfish is being one of the factors to decrease production of the goldfish. The goldfish infected with bacteria was founded in a pond in Patumbak. The study was aim to observe bacteria that might cause fish disease. The isolation of the potensial pathogenic bacteria of goldfish was utilised using the agar spread method. Identification of pathogenic bacteria was done using Vitec 2 compact. Test of water samples was conducted at the Laboratory BTKL Class 1 Medan. Two species were found as potential pathogens in the goldfish, i.e. Pseudomonas aeruginosa and Enterecoccus faecalis. Test of water quality showed that the water quality was still in permitted condition.Keywords: Bacterial pathogens, Goldfish, Pond, Water Quality